Through the looking glass of student perception: How foreign language students see teacher trait emotional intelligence and why it matters - Moskowitz, Sharona; Dewaele, Jean-Marc (Studies in Second Language Learning and Teaching, 2020)
The aim of this study is to examine how students perceive teacher trait emotional intelligence (TEI) and how those perceptions relate to students’ own self-reported attitudes and motivation. Adult students of ESL/EFL were given an online questionnaire consisting of two parts: one to provide observer-reported data on their teacher’s trait emotional intelligence and the second to measure students’ own attitudes and motivation. In total, 129 participants of 28 nationalities took part. The results showed that the perceived teacher TEI domains of teacher sociability and teacher self-control were significant predictors of student positive feelings and attitudes towards the teacher. With this paper, we make the case that observer reports of teacher TEI by students could be a valuable tool in L2 instruction by offering teachers unique insight into their own classroom behavior, thereby increasing teacher self-awareness which could lead to improved classroom practices.